Pemberdayaan Pembudidaya Ikan Melalui Pelatihan Budi Daya Ikan Nila Sistem Bioflok Untuk Mendukung Ketersediaan Protein Yang Berkelanjutan di Karawang - Suhermanto (indonesia), Achmad; Pramono Adi (indoensia), Catur; Prabowo (indonesia) et al, DH. Guntur (JURNAL KASTARA, 2025)
Indonesia, as an archipelagic country, possesses immense potential in both capture and aquaculture fisheries. Among freshwater aquaculture commodities, Nile tilapia (Oreochromis niloticus) is favored due to its fast growth, palatable taste, and ease of cultivation. However, conventional tilapia farming faces challenges such as limited land availability, excessive water usage, organic waste pollution, and high feed costs. Biofloc technology offers an innovative solution by utilizing microbial consortia to convert organic waste into edible flocs, thereby reducing feed consumption, improving water quality, and increasing sustainability. This community service initiative, conducted by the Karawang Marine and Fisheries Polytechnic, aimed to enhance fish farmers’ capacity—specifically among students at the Mumbar Huffazh Islamic boarding school—by introducing biofloc aquaculture practices. The program included training on the technical and practical aspects of the biofloc system and its application in small to medium-scale operations, particularly in land-limited rural or urban settings. Implemented on February 26, 2024, with follow-up support and evaluation, the program sought to (1) increase knowledge and skills related to efficient, eco-friendly tilapia farming; (2) foster commitment to water quality monitoring; and (3) promote sustainable aquaculture that aligns with the national Free Nutritious Food (MBG) program. The anticipated outcomes include reduced feed usage by up to 50%, shorter production cycles, enhanced fish availability, and improved livelihoods. The initiative reflects the institution’s commitment to the "Tri Dharma" of higher education through community empowerment, contributing to equitable development and protein food security.